Transmission Strategies Used by Gyrodactylus gasterostei (Monogenea) on Its Host, the Three-Spined Stickleback Gasterosteus aculeatus - Mayra I. Grano-Maldonado; Juan Moreno-Navas; Maria Amparo Rodriguez-Santiago (Fishes, 2018)
The monogenean Gyrodactylus gasterostei and its host, the three-spined stickleback Gasterosteus aculeatus, were employed as a model system to investigate the influence of gyrodactylid maturity on host transfer. Laboratory experiments included the determination of maturity (presence of a male copulatory organ) and reproductive status (presence of a daughter parasite) of the transmitting worms. Parasites with a male copulatory organ were more likely to abandon the host and attempt a host transfer. Additionally, in vivo video observation suggested that detached worms employ water turbulence to assist their effective transfer onto a new host.

Osteoblasts Display Different Responsiveness to TRAIL-Induced Apoptosis During Their Differentiation Process - Giacomina Brunetti; Angela Oranger; Claudia Carbone; Giorgio Mori; Francesca Rita Sardone; Claudio Mori; Monica Celi; Maria Felicia Faienza; Umberto Tarantino; Alberta Zallone; Maria Grano; Silvia Colucci (Cell Biochemistry and Biophysics, 2013)

The death receptor DR5 is involved in TRAIL-mediated human osteoclast apoptosis - Silvia Colucci; Giacomina Brunetti; Francesco Paolo Cantatore; Angela Oranger; Giorgio Mori; Paolo Pignataro; Roberto Tamma; Felice Roberto Grassi; Alberta Zallone; Maria Grano (Apoptosis, 2007)